Pemberian Terapi Relaksasi Benson untuk Menurunkan Tingkat Kelelahan Pasien Chronic Kidney Disease (CKD) yang Menjalani Hemodialisa - Shohibul Bahri Radiansah; Erna Rochmawati; Akhmad Zuhri (PPNI UNIMMAN, 2024)
Chronic Kidney Disease (CKD) is a long-term medical condition characterized by a decline in kidney function. Hemodialysis is one of the treatments for CKD, but it can cause biological and psychological disturbances if done over a long period of time, one of which is fatigue. This study uses a case report approach to evaluated implementation of nursing care for patients experiencing fatigue. The fatigue level measurement tool uses the FACIT version 4 questionnaire. The results of this study show that patients experience high fatigue with a score of 17,52 and after being given Benson Relaxation intervention as many as 2 meetings, the patient’s fatigue level score becomes 21,6 which means it is approaching the normal score of >31. Benson Relaxation is a complementary technique that is easy to apply and has many benefits for fatigue. There is an influence between the application of Benson relaxation on the decrease in fatigue levels of CKD patients undergoing Hemodialysis.